Sheikh Abdullah Mustafa Al Naqshbandi: His life and scientific efforts - المدرس المساعد كارزان فقي خليل كريم (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
God Almighty made the religion of Islam to be the seal of religions, and that his law, which came by the Prophet peace be upon him the last laws of heaven, and required the will of God to preserve this religion and its provisions of any alteration or distortion. Therefore, God has prepared for this conservation and attention to its causes, and the reasons for the preservation of this religion that in every time and place scientists dedicated themselves to serve and attention to it. And scientists have a great status and a high degree of God Almighty, where the elevation of their status and the highest and distinguished from the human beings, there is no doubt that the fulfillment of these scientists to revive their memory, and enlightenment books of science and benefits and arts, for this I wrote about the Sheikh who gavepeople effort to show them ways Al-Huda explains to them the provisions of their religion, namely Sheikh Abdullah bin Mustafa Al-Naqshbandi Al-Harashi. Sheikh Abdullah Al-Naqshbandi, may Allah have mercy on him, is one of the scholars of this era, he is one of the knights of Islamic sciences and Shari'a, and this is shown to those who have studied his writings, as well as the legal sciences in the field of law, economics, finance and literature, and where no one has written about his life ,in this research I interviewed his son, Dr. Sheikh Hassan Naqshbandi. In this research I presented his biography, family, scientific efforts. The research called (Sheikh Abdullah bin .)Mustafa Al Naqshbandi Al Hershmi his life and scientific efforts